(untitled) (Delta Medical College Journal, 2022)
Background: Skin diseases are common and cause a huge burden globally. Bangladesh is known to have a high prevalence of skin diseases. Considering the economic burden of the skin diseases treatment and its high prevalence, it is important to study the drug prescribing patterns in skin diseases. Objective: To evaluate the prescribing pattern of drug according to World Health Organization (WHO) prescribing indicators among the patients attending Dermatology outpatient department in two teaching hospitals. Materials and method: A cross sectional descriptive study was conducted in outpatient department of Dermatology in Dhaka Medical College Hospital (DMCH) and Sir Salimullah Medical College & Mitford Hospital (SSMC & MH) from July 2015 to June 2016. A total number of 600 prescriptions (300 from each hospital) were enrolled in the study. The general information and data were collected in the questionnaire and subjected to evaluation using WHO prescribing indicators. Results: The average number of drugs per prescription was 2.41 in DMCH and 2.38 in SSMC & MH. Only 23.72% drugs in DMCH and 27.79% drugs in SSMC & MH were prescribed by generic name. The percentage of prescriptions with antibiotics was 46% in DMCH and 45.66% in SSMC & MH. The percentage of prescriptions with an injection encountered was 0.67% and 0.33% in DMCH and SSMC & MH respectively. This study also revealed that, the percentage of drugs prescribed from the Essential Drug List (EDL) of Bangladesh was 56% in DMCH and 57.68% in SSMC & MH. Conclusion: There is need to emphasize to keep the average number of drugs as low as possible and encourage prescribing by generic name and from Essential Drug List (EDL). Delta Med Col J. Jul 2020 8(1): 9-14